RETRACTED ARTICLE: Aging exacerbates the brain inflammatory micro-environment contributing to α-synuclein pathology and functional deficits in a mouse model of DLB/PD - Michiyo Iba; Ross A. McDevitt; Changyoun Kim; Roshni Roy; Dimitra Sarantopoulou; Ella Tommer; Byron Siegars; Michelle Sallin; Somin Kwon; Jyoti Misra Sen; Ranjan Sen; Eliezer Masliah (Molecular Neurodegeneration)
Abstract Background Although ɑ-synuclein (ɑ-syn) spreading in age-related neurodegenerative diseases such as Parkinson’s disease (PD) and Dementia with Lewy bodies (DLB) has been extensively investigated, the role of aging in the manifestation of disease remains unclear. Methods We explored the role of aging and inflammation in the pathogenesis of synucleinopathies in a mouse model of DLB/PD initiated by intrastriatal injection of ɑ-syn preformed fibrils (pff). Results We found that aged mice showed more extensive accumulation of ɑ-syn in selected brain regions and behavioral deficits that were associated with greater infiltration of T cells and microgliosis. Microglial inflammatory gene expression induced by ɑ-syn-pff injection in young mice had hallmarks of aged microglia, indicating that enhanced age-associated pathologies may result from inflammatory synergy between aging and the effects of ɑ-syn aggregation. Based on the transcriptomics analysis projected from Ingenuity Pathway Analysis, we found a network that included colony stimulating factor 2 (CSF2), LPS related genes, TNFɑ and poly rl:rC-RNA as common regulators. Conclusions We propose that aging related inflammation (eg: CSF2) influences outcomes of pathological spreading of ɑ-syn and suggest that targeting neuro-immune responses might be important in developing treatments for DLB/PD.